Collective creativity and artistic agency in Colonial Latin America - Stanfield-Mazzi, Maya Selama, 1972-; Vargas-Betancourt, Margarita (University of Florida Press, 2023)
"This volume addresses and expands the role of the artist in colonial Latin American society, featuring essays that consider the ways society conceived of artists and the ways artists defined themselves"--